The geographical dispersion of inventor networks in peripheral economies - Marcelo Cano-Kollmann; Ram Mudambi; Ana Teresa Tavares (ZFW - Advances in Economic Geography, 2022)
In this paper we explore patenting activity in two peripheral economies (Portugal and Greece), to analyze the dispersion of inventor networks. Inventor networks are key conduits through which knowledge flows. Therefore, they can be critical in the catch-up process of peripheral economies - economies that belong to the group of rich countries but have weaker innovation systems. As global value chains fragment into geographically dispersed activities, opportunities arise for peripheral economies to participate in global innovation processes. However, different types of innovation activities have distinct network properties. More codifiable innovative activities can be carried out through collaboration by internationally dispersed teams. On the other hand, activities that are more dependent on tacit knowledge are likely to require the co-location of knowledge workers. This implies that innovation that relies mostly on tacit knowledge will provide limited connectivity benefits for peripheral economies' innovation systems. We hypothesize that, while this is generally true, 'leading' innovative multinational enterprises may possess more sophisticated capabilities for transnational collaboration than less innovative firms. Therefore, innovation in activities involving tacit knowledge may show different network characteristics depending on who performs them: leading firms or 'laggards'. Our results, based on data from Portugal and Greece are consistent with our hypotheses.
Keywords: 330; connectivity; Innovation; patents; Peripheral economies